Luminescence properties of a Zn(ii) supramolecular framework: easily tunable optical properties by variation of the alkyl substitution of (E)-N-(pyridine-2-ylethylidyne)arylamine ligands. Issue 111 (21st November 2016) - Dong, Yu-Wei; Fan, Rui-Qing; Chen, Wei; Zhang, Hui-Jie; Song, Yang; Du, Xi; Wang, Ping; Wei, Li-Guo; Yang, Yu-Lin
Abstract : The easily tunable luminescence properties of Zn(ii ) complexes based on the different alkyl substituents of the Schiff-base ligand have been studied in detail. Abstract : A series of different alkyl substituted of Zn(ii ) complexes, [ZnL 1 Cl2 ] (Zn1 ), [ZnL 2 Cl2 ] (Zn2 ), [ZnL 3 Cl2 ] (Zn3 ), [ZnL 4 Cl2 ] (Zn4 ), [ZnL 5 Cl2 ] (Zn5 ) (( E )- N -(pyridine-2-yl)(CMe{NPhR), where R = H, L 1 ; 2-CH3, L 2 ; 2, 6-(CH3 )2, L 3 ; 2, 4, 6-(CH3 )3, L 4 ; 2-OCH3, L 5 ) have been synthesized and characterized by single crystal X-ray diffraction, 1 H NMR, FT-IR, and EA. The X-ray diffraction analyses revealed that although are all constructed by C–H⋯Cl/π hydrogen bonds and π⋯π interactions, the dimensions of these supramolecular frameworks complexesZn1–Zn5 are quite different. ComplexesZn1 andZn5 feature 3D 5-connected 4 6 ·6 4 and 4 4 ·6 6 topology structures, respectively, while complexesZn2 andZn3 feature 2D supramolecular layer with 6 3 topology structures. ComplexZn4 exhibits two different one-dimensional helix-shaped chains. Obviously, these results show that steric hindrance has a great impact on the final structures of the supramolecular architectures. Based on these varied structures caused by different alkyl substitutions, the emission maximum wavelengths of complexesZn1–Zn5 can be tuned in a large range of 400–514 nm. The λ em shift in the red direction after the substitution of alkyl is attributed to the HOMO–LUMO energy gap of complexes being effectively decreased due to the electron-donating ability of alkyl. These results are confirmed by the density functional theory calculations.